An Adequacy Evaluation Model for Power System - Nian Liu; Buxiang Zhou; Bo Lin; Luofang Zhu; Ming Liu (Institute of Advanced Engineering and Science, 2013)
The variety of the weather condition in which a transmission and distribution hybrid system resides has a significant impact on the reliability results of power systems; therefore, model is the key point of reliability evaluation when considering weather change. This paper illustrates a model that can be utilized for the evaluation of adequacy in weather conditions, and presents a calculation method for system component failure rate in the adverse weather conditions. Using Monte-Carlo simulation which based on component state duration sampling to get the evaluation results of the power system, and provide the basis for power system adequacy analysis. Results of calculation examples show that the proposed model is feasible and effective in power system. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.2546